Perlindungan Hukum Terhadap Anak sebagai Korban Tindak Pidana Pencabulan dan Persetubuhan - Udin Nurkholis Huda; Hartoyo Hartoyo; Fitri Ayuningtyas (Lembaga Pengembangan Kinerja Dosen, 2025)
The crime of molestation and sexual intercourse against children is an act that violates social norms of politeness, religion and decency. Article 28b paragraph (2) of the 1945 Constitution of the Republic of Indonesia reads: